Geo-Jute for River Bank Protection - A Case Study - Ghosh, S K; Ganguly, P K; Debanth, S; Nag, D (Journal of Agricultural Engineering, 2006)
Geo-jute is jute matting, which has been successfully developed by needle-punched non-woven and woven techniques and has been tried for erosion control and reinforcement of soil. Plant roots trap soil particles and prevent erosion. Non-woven & Woven Jute Geo-fabrics are widely used, as these are eco-friendly, economical, biodegradable, non-toxic, non-plastic, hydrophytes, made of messy fibres and are good for draping. Jute degrades quickly and produces ligno-mass in the soil with additional nitrogen, phosphorus and potassium. Thus the fertility and texture of soil are improved. In the present field trials, NIRJAFT experimented Non-Woven and Woven Jute Geo-textiles for control of soil erosion on moderate slopes (30 Degree-15 Degree) as well as dense fabrics (two-fold) for separation and filtration for the protection of the bank of river Hooghly in West Bengal.